2022
DOI: 10.1177/15330338221105718
|View full text |Cite
|
Sign up to set email alerts
|

Application of Controlled Hypotension During Surgery for Spinal Metastasis

Abstract: With advances in tumor treatment, metastasis to bone is increasing, and surgery has become the only choice for most terminal patients. However, spinal surgery has a high risk and is prone to heavy bleeding. Controlled hypotension during surgery has outstanding advantages in reducing intraoperative bleeding and ensuring a clear field of vision, thus avoiding damage to important nerves and vessels. Antihypertensive drugs should be carefully selected after considering the patient's age, different diseases, etc, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Cancer resection surgeries usually have a complex extensive operative field. Consequently, proper control of intraoperative blood pressure results in a clearer surgical field with lower incidence of operative blood loss ( 7 ). Intraoperative hypertension can be encountered in hypertensive patients undergoing surgeries under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer resection surgeries usually have a complex extensive operative field. Consequently, proper control of intraoperative blood pressure results in a clearer surgical field with lower incidence of operative blood loss ( 7 ). Intraoperative hypertension can be encountered in hypertensive patients undergoing surgeries under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…It was noticed that the rapid infusion of dexmedetomidine loading dose over less than 10 min can lead to hypertension through activating peripheral α2a receptors, while slow infusion results in the activation of central α2a receptors with the subsequent inhibition of noradrenaline release and lowering of HR and blood pressure ( 5 ). Moreover, dexmedetomidine infusion has a neuroprotective effect with reducing cerebral oxygen consumption and decreased incidents of cognitive dysfunction postoperatively ( 7 ). In the current study, we observed that patients who received dexmedetomidine infusion showed more hemodynamic stability with fewer episodes of intraoperative hypotension, tachycardia, and rebound elevation of blood pressure after discontinuation of the drug infusion.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by the World Health Organization, the International Agency for Research on Cancer predicts that there will be 28.4 million new cases of cancer worldwide by 2040, an increase of 47% compared to 2020 [ 2 ]. Recently, the incidence of cancer in China has been steadily increasing [ 3 ], and what’s more, virtually all cancer types are becoming more common in younger age groups [ 4 ]. According to the Chinese Cancer Control Center [ 5 ], more than 1.4 million new cancer survivors are born every year.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled hypotension has advantages, including reducing intraoperative bleeding, ensuring clear surgical visibility, avoiding damage to important nerves and blood vessels, shortening the operation time, and lessening tissue edema; hence, it has been widely used in various clinical operations. [ 4 , 5 ] However, it is seldom used in TKA. Certainly, there are other reasons for the insufficient study of controlled hypotension technology in TKA.…”
Section: Introductionmentioning
confidence: 99%